2013
DOI: 10.1021/jp311443s
|View full text |Cite
|
Sign up to set email alerts
|

Facile Synthesis of Face Oriented ZnO Crystals: Tunable Polar Facets and Shape Induced Enhanced Photocatalytic Performance

Abstract: This study reports on the formation of unique oriented ZnO structures (face oriented hexagonal discs, 3D-trapezoids, rings, doughnuts, and hemispheres) with tunable percentage of exposed polar facets synthesized via a simple hydrothermal route in aqueous base environment. The significance of the synthetic strategy is the generation of exotic structures without using any templates/structure directing agents and successful realization of morphologies with increased polar to nonpolar facet ratio. Detailed investi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
89
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 136 publications
(92 citation statements)
references
References 52 publications
3
89
0
Order By: Relevance
“…Moreover, the defect density increased with the amount of polar surfaces because the sample with the highest Cu fraction had undergone more etching because of the increased Cl À content, leading to more oxygen vacancies. Li et al and Boppella et al have shown that polar surfaces in ZnO nanostructures result in a large amount of oxygen vacancies that capture photogenerated electronehole pairs, reducing the recombination rate [59,60]. Furthermore, it has also been also shown that doping with Cu enhances ferromagnetism in ZnO due to the creation of surface defects and oxygen vacancies [61].…”
Section: Photoluminescencementioning
confidence: 99%
“…Moreover, the defect density increased with the amount of polar surfaces because the sample with the highest Cu fraction had undergone more etching because of the increased Cl À content, leading to more oxygen vacancies. Li et al and Boppella et al have shown that polar surfaces in ZnO nanostructures result in a large amount of oxygen vacancies that capture photogenerated electronehole pairs, reducing the recombination rate [59,60]. Furthermore, it has also been also shown that doping with Cu enhances ferromagnetism in ZnO due to the creation of surface defects and oxygen vacancies [61].…”
Section: Photoluminescencementioning
confidence: 99%
“…The excellent photo-catalytic properties were due to the high percentage of polar facets and high oxygen vacancy concentrations which decreased in the order of rose-like > hexagonal prisms > ZnO plates. Later, many other groups synthesized different morphologies of ZnO and claimed that the enhanced photo-activities were due to the high exposure of polar facets and large number of oxygen vacancies [173][174][175][176][177][178].…”
Section: Degradation Of Methylene Blue (Mb)mentioning
confidence: 99%
“…The exposed crystalline face is noticeably different for ZnO particles with different morphologies: the more specific sites they have, the more their activities become. The unique ZnO nanodisks with high (0001) facet population and small surface area show better photocatalytic activity than other crystalline faces [24,25]. In this work, single-crystalline nature of ZnO and La-doped ZnO nanorods is of preferential growth along the [001] direction.…”
Section: Methodsmentioning
confidence: 81%
“…Photocatalytic activity of the photocatalyst is mainly determined by several factors: morphology, BrunauerEmmett-Teller (BET) surface area, crystalline facet, and dopant [6,16,18,[23][24][25]. Spherical ZnO has higher photocatalytic activity than flower-like ZnO, because it has rather higher specific surface area and pore volume than nanostructured flower shape [23].…”
Section: Methodsmentioning
confidence: 99%